THE EFFECT OF ADDITIONAL SEAWEED FLOUR (Eucheuma cottonii) ON THE QUALITY OF CATFISH (Clarias sp.) ROULADE - Aghitia Maulani; Asriani Asriani; Narila Maryuni; I Ketut Sumandiarsa (Universitas Mataram, 2025)
Catfish (Clarias sp.) is a popular freshwater fish that contains higher protein than some types of animal meat. Seaweed (Eucheuma cottonii) has high nutritional content such as minerals and fiber. The high nutritional content of Eucheuma cottonii as a potential functional food source in the development of food products, one of which is processed into seaweed flour which is added to catfish rolade products. The objectives of this study were to analyze the quality of dried seaweed and fresh catfish, process seaweed flour and catfish rolade and analyze the quality of seaweed flour and catfish rolade, and determine the selected formula. The results of sensory tests of dried seaweed raw materials were 8, CAW 59,65%, and water content 34,19%, Organoleptic value of fresh catfish 9. The results of seaweed flour water content 6,39%, ash content 24,52%, fat content 0,24%, protein content 2,72%, carbohydrate 66,13%, crude fiber 22,21% and and around 360,27 mPa s. The results of catfish rolade with the addition of E. cottonii flour included water content 65,90%, ash content 2,90%, fat content 2,84%, protein content 17,79%, carbohydrate 10,57%, crude fiber 0,56%, ALT 5.21 x 101 kol/g, and physical test hardness 6562,99 gf. The selected formula is catfish roulade with the addition of 3,5% E. cottonii seaweed flour.